Non-infectious thrombotic endocarditis associated with chronic rheumatic heart disease and disseminated tuberculosis - Aravind Sekar; Sanjeev Naganur (University of São Paulo, 2021)
Rheumatic heart disease is still common in developing countries and requires prompt intervention to prevent chronic complications. Vegetations in rheumatic heart disease might be due to acute episodes of rheumatic fever itself or due to either infective endocarditis (IE) or Non-infectious thrombotic endocarditis (NITE). Each form of vegetations has specific pathological characteristics on gross and microscopic examination. However, clinically IE and NITE may have overlapping signs and symptoms. A chance of misdiagnosis of NITE as culture-negative infective endocarditis is higher if the former present with infective symptoms like fever. NITE of valves can be due to underlying associated malignant neoplasm, particularly mucinous adenocarcinoma, pneumonia, cirrhosis, autoimmune disorders, and hypercoagulable state. The coexistence of tuberculosis, non-infectious thrombotic endocarditis and rheumatic valvular heart disease was rarely documented in medical literature. We describe a case of chronic rheumatic heart disease with vegetations in the posterior mitral valve leaflet, treated as culture-negative infective endocarditis, which, at autopsy, reveals the presence of Nonbacterial thrombotic endocarditis vegetation over calcified, fibrosed mitral valve leaflets and associated disseminated tuberculosis along with classic pathological sequela findings of chronic rheumatic mitral valvular heart disease in lungs and liver.